Dampak Kebakaran Hutan Terhadap Flora Dan Sifat Tanah Mineral Di Kawasan Hutan Kabupaten Pelalawan Provinsi Riau - Basuki Wasis; Bambang Hero Saharjo; Robi Deslia Waldi (Jurnal Silvikultur Tropika, 2019)
Forest fires cause the death of flora, soil damage and smoke disasters. The research was corected at the productivity forest and soil samples were taken through purposive sampling. The result of research show that forest fires cause the death of flora by 100% and erosion occurring at the dept of 5-10 cm. Forest fires cause a significant increase in pH, Ca and Mg mineral soils, and reduce organic C, total microorganisms, total fungi and soil respiration significantly. Forest fires increase soil pH and soil fertility due to ash remaining combustion. The residual combustion ash comes from organic material (natural forest biomass and organic matter) which is burned was which of nutrient needed fan the growth of the vegetation in the forest.Keywords: forest fires, mineral soils, soil fertility, soil properties